1996
DOI: 10.1111/j.1365-2044.1996.tb07787.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose—response and minimum time to satisfactory intubation conditions after mivacurium in children

Abstract: SummaryWe assessed neuromuscular blocking effects and tracheal intubation conditions following mivacurium in 121 anaesthetised children aged 1-10 years. The study was conducted in three parts. Parts Key wordsAnaesthesia; paediatric. Intubation; tracheal. Neuromuscular relaxants: mivacurium.Mivacurium is a newer non-depolarising neuromuscular blocking drug with a short duration of action due to its rapid metabolism by plasma cholinesterase [I, 21. In view of its short duration of action, mivacurium may be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…However, thiopentone and nitrous o~de without a neuromuscular blocker have been shovm to produce poor or impossible intubation conditions in children. 9 No other studies have compared intubation conditions following mivacurium administration during different types of anaesthesia ha paediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, thiopentone and nitrous o~de without a neuromuscular blocker have been shovm to produce poor or impossible intubation conditions in children. 9 No other studies have compared intubation conditions following mivacurium administration during different types of anaesthesia ha paediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…In children anesthetized with thiopental-nitrous oxide, satisfactory intubating conditions were observed in 98 and 100% of cases 90 and 70 s after the administration of 2 Â ED 95 doses of mivacurium or rocuronium, respectively [26,27]. Similarly, in a study of 60 children aged 2-7 years, good/excellent intubating conditions were achieved in all patients at 1 MAC anesthesia with sevoflurane 2 min after injection of rocuronium 0.3 mg/kg (around 1 Â ED 95 ) [28].…”
Section: Balanced Anesthesia With a Nondepolarizing Muscle Relaxantmentioning
confidence: 97%
“…Mivacurium 0.2 mg/kg (around 2 Â ED 95 ) provides satisfactory intubating conditions in 98% of children 90 s after administration during thiopental-nitrous oxide anesthesia [26]. Onset of maximum block occurs in 1-2 min and 25% recovery in 9-10 min.…”
Section: Mivacuriummentioning
confidence: 99%
“…Mivacurium 200 μg/ kg IV provides good intubating conditions after 90 s in children [ 213 ]. Several studies showed that fentanyl decreased the number of attempts and the incidence of desaturation during tracheal intubation in premature and full-term neonates [ 185 , 214 ].…”
Section: Muscle Relaxants For Tracheal Intubationmentioning
confidence: 99%